SOCIAL AND FINANCIAL EFFICIENCY OF LEMBAGA PERKREDITAN DESA - Baskara, IGde Kajeng; Suarjaya, AnakAgung Gede (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 1, Februari 2022 (pp.1-161), 2022)
Efficiency in managing microfinance institutions in villages has an impact upon the social economic level within village communities. Other than that of efficiency in financial performance, efficiency in social performance has gained significant amount of attention.  Village Credit Institution or Lembaga Perkreditan Desa (LPD) is considered a Microfinance Institution or  Lembaga Keuangan Mikro (LKM) that is based on Balinese village culture in Bali, Indonesia. This research will measure the efficiency of financial and social performances of 38 of the largest Village Credit Institution in Bali that have assets accumulated above 100 Billion Rupiah. The measurement for the efficiencies performance will utilize a Data Envelopment Analysis (DEA) model in which analyzes the total assets, operational costs and the number of employees as part of the input and operational income, the number of loans, the number of savings and social performances as part of output. The results of this research can show that social and financial performance in Bali having efficient management.